FlashMob: Distributed adaptive self-assembly - Sykes,D; Magee,J; Kramer,J (2011)
Autonomous systems need to support dynamic software adaptation in order to handle the complexity and unpredictability of the execution environment, and the changing needs of the end user. Although a number of approaches have been proposed, few address a key issue: that of distribution. In this paper we seek to overcome the limitations of centralised approaches. We build on our previous work on adaptive self-assembly within the three-layer model for autonomous systems to provide a decentralised technique for self-assembly. To achieve this in a fault-tolerant and scalable manner, we use a gossip protocol as a basis. While no central or leader node is aware of the full space of solutions, gossip ensures that agreement on a particular solution - in this case a component configuration - is reached in a logarithmic number of steps with respect to the size of the network. © 2011 ACM.